Content creator hub - Constantinides, Michael Graham George (My University, 2017)
This research report is to investigate the physical realm of online content creation as well as the effects content creation and social media has in a South African context. The objective of this research report is to identify the areas in which Architecture can better support the new generation of online content developers. With the fast paced development of the Internet and digital technology, Architecture needs to form new ideologies, typologies and tectonics in order to stay relevant. A space that’s is the pivoting point between two worlds: online and offline. The result of this study is to create a new typology to fit within the Internet industry within South Africa and to be able to leapfrog the country and it’s specific design site in Braamfontein, Johannesburg, into the Internet territory. A space is needed that will be the intersection of the physical and the online world, a space that becomes a connection node with a presence in both worlds. The Content Creator Hub, which is an architectural space that not only facilitates the creation of online content but also the sharing of skills, collaborative efforts, exposure to business practises, business people and business opportunities, access to tools and equipment as well as access to a conducive space. The formation of an actual place where a new form of creative artists exist and are able to create, learn, share, connect, collaborate and help innovate. Furthermore, there is an opportunity to take the philosophical ideas and approaches of The Content Creator Hub to implement them into an urban scheme and in a Southern African context. Architecture plays an important role not only by generating content but also by accelerating the action.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa; Public spaces--South Africa; Social media--South Africa